UJI SITOTOKSIK DENGAN METODE BRINE SHRIMP LETHALITY TEST DAN PROFIL METABOLIT SEKUNDER DARI EKSTRAK BIJI BUAH BERENUK (Crescentia cujete Linn) - Afdhil Arel (Universitas Wahid Hasyim Semarang, 2018)
ABSTRACTThe purpose of this research is to find out the profile of secondary metabolite contained in the extract of seeds (Crescentia cujete Linn.) And cytotoxic test against shrimp larvae Artemia salina Leach by BSLT method. Phytochemical tests showed that the extract be expected contained the terpenoid, alkaloid, phenolic, secondary metabolite compounds. The results of qualitative analysis with positive TLC contains phenolics. The result of identification with Spectrophotometer UV-visfor determination of α max from berenuk seeds extract consisted of 3 peaks with α max 326 nm, 258 nm, 222 nm be expected terpenoid compound, alkaloid, and phenolic. The results of toxicity test using shrimp larvae (Artemia salina leach) were divided into 4 groups: 1 control group and 3 groups of concentration series. The concentration of test solution used was 1,000, 100 and 10 μg / ml. The shrimp larvae mortality was observed after 24 hours of treatment. Based on the analysis with probit method, LC50 value of seed extract berenuk to shrimp larvae Artemia salina Leach is equal to 82,30 μg/ml. This shows that the extract of berenuk berries is toxic to shrimp larvae Artemia salina Leach, presence to terpenoid content, alkaloids and phenolics in the extract of seeds berenuk.Keywords : Secondary metabolite; Cytotoxic; BSLT.